2010
DOI: 10.1007/s10565-010-9153-7
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and posttranscriptional regulation of CYP1A1 by vanadium in human hepatoma HepG2 cells

Abstract: We recently demonstrated that V(5+) downregulates 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD)-mediated induction of Cyp1a1 mRNA, protein, and catalytic activity levels in Hepa 1c1c7 cells through transcriptional mechanism. Therefore, it is important to investigate whether similar changes occur in humans. For this purpose, we examined the effect of V(5+) (as ammonium metavanadate, NH(4)VO(3)) on the expression of aryl hydrocarbon receptor (AhR)-regulated gene; cytochrome P450 1A1 (CYP1A1) at each step of the AhR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…The data are expressed the means 6 S.D. causes a significant upregulation of CYP1A1/2 mRNAs expression [Misaki et al, 2007;Abdelhamid et al, 2010;Zhang et al, 2011]. Consistent with these results, DiMeDBC and mainly N-MeDBC increased substantially the CYP1A1/2 mRNA levels in HepG2 cells.…”
Section: Discussionsupporting
confidence: 81%
“…The data are expressed the means 6 S.D. causes a significant upregulation of CYP1A1/2 mRNAs expression [Misaki et al, 2007;Abdelhamid et al, 2010;Zhang et al, 2011]. Consistent with these results, DiMeDBC and mainly N-MeDBC increased substantially the CYP1A1/2 mRNA levels in HepG2 cells.…”
Section: Discussionsupporting
confidence: 81%
“…Cytochrome P4501A is a monooxygenase involved in xenobiotic biotransformation and detoxification of many PAHs, PCBs and dioxins and is induced by the binding of these compounds with aryl hydrocarbon receptor (AhR), that is, a cytosolic ligand-activated transcription factor Hahn 2001). The induction of Cyp1a may then be regulated at various post-transcriptional steps (Abdelhamid et al 2010;Amara et al 2010). Cytochrome P4501A can also be activated by other pathways and plays a strong role in steroid hormone biosynthesis, tryptophan and retinol metabolism (review in Monostory et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports from our laboratory demonstrated that V 5+ was able to decrease the TCDD‐mediated induction of Cyp1a1 and Nqo1 at mRNA, protein, and catalytic activity levels in the mouse hepatoma Hepa 1c1c7 cells (Anwar‐Mohamed and El‐Kadi, ; Anwar‐Mohamed and El‐Kadi, ) and in human hepatoma HepG2 cells (Abdelhamid et al ., , ). However, it was not reported previously if V 5+ could affect TCDD‐mediated induction of Cyp1a1, Cyp1a2 and Cyp1b1 mRNA, protein or catalytic activity levels in the kidney, lung or heart of C57BL/6 mice.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, few studies have examined the combined toxicological effects of these ligands with heavy metals such as V 5+ . At the in vitro level, we recently reported that V 5+ was able to decrease the TCDD‐mediated induction of Cyp1a1 and Nqo1 at mRNA, protein and catalytic activity levels in the mouse hepatoma Hepa 1c1c7 cells, which were derived from BW7756 mouse hepatoma that arose in a C57BL/6 mouse (Anwar‐Mohamed and El‐Kadi, , ) and in human hepatoma HepG2 cells, which were derived from the liver tissue of a 15‐year‐old Caucasian American male with a well‐differentiated hepatocellular carcinoma (Abdelhamid et al ., , ). However, to the best of our knowledge, there has been no previous attempt to examine the effect of V 5+ on the regulation of AhR‐regulated genes in the presence and absence of TCDD in extrahepatic tissues in vivo .…”
Section: Introductionmentioning
confidence: 99%